Ancestors : Life, Death, and Descendants of Quebec City's Anglophones - Morrin Centre (2008)
Quebec City’s cemeteries have lots to say about our ancestors and the past. They are places of remembrance for those close to the departed, but they are also a storehouse of memories for the whole community. Cemeteries are closely linked to religious belief : They express a particular vision of the world, a set of values and a culture.

Building the City : The Influence of English Speakers on Quebec City's Architecture - Morrin Centre (2008)
Quebec City is praised for its quintessential Frenchness, yet a closer look at its architecture reveals a city with a strong British influence. Ninety-five per cent of the city was built or modified after the British conquest in 1759. In the middle of the ninete nth century, half the people in the Upper Town were English speakers, and they left a clear mark on the built environment. Many of the city’s important landmarks, from the Château Frontenac to the Price Building, were designed by English-speaking architects.

Les ancêtres : vie, mort et descendance des anglophones de la ville de Québec - Morrin Centre (2008)
Les cimetières de la ville de Québec constituent une mine de renseignements précieuse à propos de nos ancêtres et du passé. Ils sont des lieux de mémoire, tant pour les proches des disparus que pour la collectivité. Étroitement liés à une religion, les cimetières sont l’expression tangible d’une vision du monde, d’un ensemble de valeurs, d’une culture.

Les bâtisseurs : l'influence anglophone sur l'architecture de Québec - Morrin Centre (2008)
Bien que l’on vante le caractère français de Québec, son architecture a subi une influence anglaise considérable : 95 % des édifices sont construits ou modifiés après 1759, suite à la Conquête. Au milieu du 19e siècle, la moitié des habitants de la Haute-Ville sont anglophones et leur présence marque le patrimoine bâti de la ville. De nombreux monuments caractéristiques de Québec, du Château Frontenac à l’édifice Price, sont conçus par des architectes anglophones.

Les gens de foi : la vie religieuse des anglophones à Québec - Morrin Centre (2008)
Cette visite vous permet d’en apprendre plus sur les anglophones de Québec à travers la découverte de leurs lieux de culte et de leurs pratiques religieuses. Les distinctions entre les différentes croyances seront examinées et vous aurez ainsi une meilleure compréhension du paysage religieux de Québec.

Les gens du fleuve : la vie des anglophones sur les rives du Saint-Laurent - Morrin Centre (2008)
L’historien grec Hérodote disait de l’Égypte qu’elle était un « don du Nil » tant ce fleuve était important dans la vie des Égyptiens. De la même façon, on pourrait dire que Québec est un don du Saint-Laurent. Le Saint-Laurent était le « boulevard » des Autochtones, premiers habitants du territoire, avant de devenir la voie d’accès des explorateurs Français. Il est un facteur déterminant dans le choix de Samuel de Champlain d’établir une colonie à Québec, car il y voyait une route vers la Chine.

People and Faith : The Religious Life of English Speakers in Quebec City - Morrin Centre (2008)
Through this tour, you’ll learn about Quebec City’s anglophones through their places of religious worship and practice. We’ll look at distinctions between different forms of belief and you’ll gain a better understanding of Quebec’s religious landscape.

People of the River : Anglophone Life on the St. Lawrence - Morrin Centre (2008)
The Greek historian Herodotus summed up Egypt’s dependence on its great river by calling the country a “gift of the Nile.” In the same way, it could be said that Quebec is a gift of the St. Lawrence. The St. Lawrence was the “boulevard” of the territory’s first inhabitants, the Aboriginal people. Then it became the access route for French explorers. Samuel de Champlain thought it was a route to China, and this was a determining factor in his decision to found a colony at Quebec.

Rediscover Quebec City's Anglo Heritage Through Four Self-Guided Tours / Redécouvrez le visage anglophone de Québec à l'aide de quatre visites autoguidées - Morrin Centre (2008)